Trademark Protection in Metaverse: Evaluating Indonesia’s Legal Framework for Well- Known Marks on Roblox - Azairin, Maudy Prima; Suryahartati, Dwi; Oktaviarni, Firya (Jurnal Ilmiah Kebijakan Hukum, 2025)
The rise of the Roblox gaming platform within the Metaverse presents new challenges for trademark protection in Indonesia. Users frequently create, trade, and sell virtual goods incorporating well-known marks without authorization, raising concerns about the adequacy of Trademark Act No. 20 of 2016 in addressing digital trademark violations. This study aims to evaluate Indonesia’s legal framework for protecting well-known marks in virtual spaces and assess its effectiveness in preventing unauthorized use on platforms like Roblox. Using a normative juridical approach, the research analyzes the current legal provisions, particularly the scope and interpretation of Articles 1, 21, and 83 of Law No. 20 of 2016, and also identifies normative gaps in addressing violations involving virtual goods and digital environments. The findings reveal that while the Trademark Act provides a foundation for brand protection, it lacks explicit regulations for virtual goods and digital environments, leaving well-known marks vulnerable to misuse. To address these challenges, the study recommends broadening key legal definitions within the Trademark Act and enhancing preventive measures on Roblox, such as stricter verification and enforcement systems. Strengthening Indonesia’s trademark regulations in response to technological advancements is essential to ensure comprehensive intellectual property protection. Theoretically, the study contributes to the discourse on adapting IP law to digital realities. Practically, it offers policy insights for legislators and platforms to prevent misuse of well-known marks in virtual spaces.